Report of the Planning Commission Research Project on: Anti-Poverty Programmes in Uttar Pradesh: An Evaluation - Planning Commission (Planning Commission)
The most significant research inputs into this study came from the field team led by Mr. K. B. Singh, former Deputy Director, NSSO, and which included Sharat Sharma, Srinivas Pandey, Mahesh Pal, Kishori Lal and Suresh Chandra. This team spend several tireless months in the field and extensively documented the working of the rural institutions and the poverty alleviation programmes. They were part of numerous brain storming sessions in which ideas floated at the Working Group or Steering Group meetings were discussed thread-bare based on the extensive field observations of members of the team. Excellent computing support for the study was provided by Dr. Nand Kishore Singh, assisted by Sharat Sharma, Mahesh Pal and Amar Singh Yadav. Sanghita Bhattacharya provided invaluable editorial assistance.
Institute For Human Development